Validasi Kurkumin Hasil Isolasi Rimpang Kunyit Dengan Kromatografi Cair Kinerja Tinggi Photodiode Array Detector - Ida Nur Farida; Annisa Muliya (Jurnal Pengelolaan Laboratorium Pendidikan, 2023)
Curcumin is the main compound in turmeric and has problems in its stability. The analytical method used to determine curcumin levels is by using high performance liquid Chromatography (HPLC) Photodiode Array Detector (PDA). HPLC has a high separation capability and good reproducibility with a low detection limit. The purpose of this research is that the isolation curcumine determined by HPLC-PDA and has been validated can be applied as a standard in quantitative analysis in the laboratory. The validation parameters specified include accuracy, precision, linearity, detection limits and quantification limits. The results of HPLC-PDA research used acetonitrile mobile phase condition : buffer phosphate pH 3,5 (70:30 v/v), flow rate of 1 mL/min, wavelength 426 nm showed curcumin from isolation had resolution (Rs= 5.7172), linearity (r=0.9991), accuracy (0.5 and 1 ppm), presicion at a concentration of 5 ppm %RSD < 20.0%, and BD values also BK are 0.1122 and 0.3401 ppm. Validation of curcumin from isolation using HPLC-PDA has the requirements as a good validation and can be used as a reference in the laboratory.